Growth and maintenance respiration in whole plants, shoots and roots of maize and rice - Machado, Eduardo Caruso; Pereira, Antonio Roberto (Pesquisa Agropecuaria Brasileira, 2014)
Maintenance respiration coefficient (M) and conversion efficiency (Y) of either the whole plant or its organs, roots and tops, were determined for two maize (HS1227 and HS7777) and two rice cultivarsa (IAC-165 and IAC-899), through the carbon balance technique of seedlings grown in nutrient solution in controlled growth chamber. Values of Y, either for the whole plant or the tops, indicated that the photosynthetic pathway (C3 or C4) did not interfer with the conversion process. Regardless of cultivar Y was greater for the tops while M was greater for the roots. Therefore, such coefficients should be considered for each organ of the plant because an overall coefficient for whole plant obscures the physiological differences of each organ.
Keywords: carbon balance; plant growth model photosynthesis; ionic absorption